Total synthesis of dehaloperophoramidine using a highly diastereoselective Hosomi–Sakurai reaction. Issue 71 (10th August 2016) - Wilkie, Ross. P.; Neal, Andrew R.; Johnston, Craig A.; Voute, Nicholas; Lancefield, Christopher S.; Stell, Matthew D.; Medda, Federico; Makiyi, Edward F.; Turner, Emma M.; Stephen Ojo, O.; Slawin, Alexandra M. Z.; Lebl, Tomas; et al.
Abstract : Synthesis involving diastereoselective Hosomi–Sakurai reaction to install the contiguous quaternary stereocentres. Abstract : The synthesis of dehaloperophoramidine, a non-halogenated derivative of the marine natural product perophoramidine, and its biological activity towards HCT116, HT29 and LoVo colorectal carcinoma cells is reported. A [3, 3]-Claisen rearrangement and an epoxide opening/allylsilylation reaction installed the contiguous all-carbon quaternary stereocentres with the required relative stereochemistry.